Onset of Labour Epidural Analgesia With Low-dose Bupivacaine and Different Doses of Fentanyl. Issue 3 (September 2018) - Vedagiri Sai, R.; Singh, S.I.; Qasem, F.; Nguyen, D.; Dhir, S.; Marmai, K.; Adam, R.; Jones, P.M.
Abstract : ( Anaesthesia 2017;72:1371–1378) While low-concentration local anesthetic solutions combined with opioids have been shown to decrease motor block without affecting the quality of labor analgesia, the onset of analgesia may be delayed when using these solutions. Previous studies have suggested that the onset of labor analgesia may be improved by the addition of a fentanyl bolus to the initial epidural dose. However, previous studies that evaluated the onset of time of epidural labor analgesia used higher concentrations of local anesthetics than are commonly used in current practice. This dose-comparison study aimed to evaluate the onset of epidural labor analgesia with different doses of fentanyl (20, 50, and 100 μg) administered with a low-concentration bupivacaine (0.08%) solution.